Pengaruh Disiplin Terhadap Kinerja Pegawai Pada Unit Pelaksana Teknis Daerah (UPTD) Puskesmas Kecamatan Muara Uya Kabupaten Tabalong - Reza Fahrepi; Karlina Karlina; Raudah Raudah (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to determine the influence of discipline on employee performance at the UPTD Community Health Center, Muara Uya District, Tabalong Regency. The sample in this study were employees at the UPTD Community Health Center, Muara Uya District, Tabalong Regency using a saturated sampling technique, 69 employees as the sample in the study were given a questionnaire consisting of 15 statements. The responses to this questionnaire were tested for validity and reliability before carrying out multiple linear regression analysis using the SPPS application. The results of submitting the instrument, namely the questionnaire, show that the 15 statement items are valid because rcount > rtable (0.237). Apart from that, all statements are reliable because Cronbach's alpha (a) > 0.6 (0.970 > 0.6). The regression equation obtained is Y = 0.034 + 0.304 X1 + 0.321 X2 + 0.378 X3. The multiple correlation coefficient (R) value is 0.928, which means that the correlation is very strong between the variables Preventive Discipline (X1), Corrective Discipline (X2), and Progressive Discipline (X3) on Employee Performance (Y). The coefficient of determination (Adjusted R2) value of 0.858 or 85.8% shows the magnitude of the variables Preventive Discipline (X1), Corrective Discipline (X2), and Progressive Discipline (X3) on Employee Performance (Y) of 85.8% while the rest is explained by other variables not included in this study were (100-85.8) % = 14.2%. Simultaneous testing shows that fcount > ftable 130.664 > 2.75 or p-value (fcount) < α (0.000 < 0.05) H0 is rejected Ha is accepted so it can be concluded that there is a significant influence between the Discipline (X) variables which consist of Preventive Discipline (X1), Corrective Discipline (X2), Progressive Discipline (X3), simultaneously influence employee performance (Y) at the UPTD Pukesmas, Muara Uya District, Tabalong Regency. Next, a partial test was carried out which showed the value of tcount > ttable for the Preventive Discipline (X1) variable, namely 3.925 > 1.997, Corrective Discipline (X2) namely 3.020 > 1.997, and Progressive Discipline (X3) namely 3.132 > 1.997 which had a significant effect on Employee Performance (Y) . Thus it is proven or H0 is rejected and Ha is accepted. Based on the tcount value, the variable Preventive Discipline (X1) is the highest compared to Progressive Discipline (X3), and Corrective Discipline (X2) has a more dominant influence on Employee Performance (Y) at the UPTD Community Health Center in Muara Uya sub-district, Tabalong Regency